(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The antimicrobial peptides (AMPs) are integral portion of the human’s innate immune system showing broad-spectrum antimicrobial roles. AMPs are used for antimicrobial therapy due to the increase in the cases of resistance towards conventional antibiotics. Unfortunately, resistance towards AMPs and their derivatives are also showing an increase. In this paper, the flowers of the vegetable Asparagus racemosus were evaluated for its anti-microbial activity on two species of the genus lactobacillus, Lactobacillus acetotolerans & Lactobacillus acidifarinae. Firstly, various extracts of Aqueous, methanol, ethanol, butanol were made. The AMP, Cecropine A was chosen as positive control & the Dimethyl sulfoxide (DMSO) was chosen as the negative control. Then the paper discs were soaked in these extracts and were kept on the lawn culture. After 24 hours, the ethanolic extract showed the highest inhibition whereas DMSO showed the least activity. These results open up possibility that this common vegetable can be utilized for the commercial production of anti-microbial agents.